EMPOWERMENT OF GREAT PARENTS IN THE IMPORTANCE OF MAINTAINING THE HEALTH OF EARLY CHILDHOOD AS A STRATEGY TOWARDS ZERO STUNTING - Martha Lowrani Siagian; Devi Aprilia; Lina Mahayaty; Sendy Firza Novilia Tono (Community Development Journal, 2023)
The number of stunting incidents is still found in the city of Surabaya. Stunting is a concern that needs to be addressed immediately because it concerns the quality of human resources. Stunting, apart from the risk of low physical growth and susceptibility to disease, also causes disrupted to cognitive development which will affect children's intelligence and productivity levels in the future. The causative factors are lack of nutritional intake, infectious diseases, mothers' lack of knowledge about stunting, false parenting patterns, poor sanitation and hygiene and poor health services as well as a lack of public awareness of children with stunting because they thought children still carry out normal activities. Method : from these phenomenon, health workers keep doing collaboration with the government are expected to continue to support Great Parents School (SOTH) activities with an emphasis on empowering parents as participants, health education which aims to provide knowledge and information to parents so they can prevent and overcome the problem of stunting towards zero stunting. The results and discussion : of the activities of this great parent empowerment program can be implemented and all participants' level of knowledge has increased, as indicated by: participants have knowledge about: (a) routine activities carried out by parents to maintain health during pregnancy, when the child is still a baby and when the child is already big; (b) types of diseases that often occur in early childhood, and (c) how to treat diseases in early childhood. Conclusion : this community service activity is of course carried out because of support from various parties, and received a positive response from the community, of course it has a very big influence in increasing public awareness in preventing stunting towards zero stunting.